IMPLEMENTING SMART STRATEGY TO ENHANCE THE READING COMPREHENSION OF BIOGRAPHY TEXTS OF THE TENTH GRADERS (RETAIN, 2017)
IMPLEMENTING SMART STRATEGY TO ENHANCE THE READING COMPREHENSION OF BIOGRAPHY TEXTS OF THE TENTH GRADERS Desi Arinda English Language Teaching, Language and Art Faculty, State University of Surabaya desiarinda95@gmail.com Dra. Theresia Kumalarini, M.Pd. English Language Teaching, Language and Art Faculty, State University of Surabaya kumala_rini52@yahoo.co.id Abstract Reading plays a crucial role in English education. Not only can it enlarge the learners’ knowledge of English grammatical structure and vocabulary, it can also be the way to get information. In fact, ones may listen or watch or even read to gather information they need. Yet written information is easier to digest because it will avoid misunderstanding due to the misinterpretation of words being listened. As reading English texts is considered challenging for students whose English comes as a foreign language, teachers must introduce some strategies to ease the students read the texts. SMART, a reading strategy developed by Buehl (2001), was rarely used in Indonesian EFL classes. Thus, this study aims to know whether the reading comprehension skill of students who are taught by implementing SMART strategy differs significantly from those taught conventionally. This study employed quasi-experimental design specifically the non-randomized control group, pretest-posttest design. It was chosen because the subjects were organized into classes which was impossibly picked random due to the limited access. The subjects were the tenth graders whose sample was done by cluster sampling. The instruments for collecting the data were tests: a pretest (to know whether both groups were equal) and a posttest (to find out the significant difference after using the strategy). After the data were collected, they were analyzed statistically using SPSS 20. The result showed that SMART strategy helped students read biography texts. It was found that significant difference exists in the reading ability between students who were taught by implementing SMART strategy and those who were not taught so. The mean score the experiment group is higher than that of the controlled one. The experiment group got 77.875 while he controlled group got 69.625. Further, the result of p value in Levene test showed that there is a significant difference between the two groups by the value of 0.009 which is far less than 0.05. The category of effect given by SMART strategy to the students who implemented it is moderate since it scored 0.11 in its eta square. Keywords: SMART strategy, reading comprehension, biography texts Abstrak Membaca memiliki peranan penting dalam dunia pendidikan bahasa Inggris. Dengan membaca, pengetahuan mengenai tata bahasa Inggris akan meningkat. Selain itu, membaca juga bisa menjadi salah satu cara untuk memeroleh informasi. Di samping membaca, sebenarnya mendengarkan juga bisa menjadi media lain untuk memeroleh informasi. Akan tetapi, informasi tertulis yang dibaca akan lebih mudah dipahami karena dapat meminimalisir kesalahpahaman yang disebabkan oleh interpretasi yang salah terhadap kosa kata bahasa Inggris yang didengarkan. Sebagai bahasa asing, membaca teks yang berbahasa Inggris masih dianggap sebagai hal yang menantang bagi siswa sehingga guru di sini bertugas untuk memperkenalkan strategi membaca yang dapat membantu mereka memahami bacaan berbahasa Inggris tersebut. Buehl (2001) mengembangkan sebuah strategi yaitu SMART yang masih jarang digunakan pada kelas bahasa Inggris di Indonesia. Oleh karena itu, penelitian ini bertujuan untuk mengetahui perbedaan signifikan antara siswa yang diajar menggunakan strategi SMART dengan siswa yang tidak diajar demikian. Penelitian ini menggunakan desain quasi-experimental khususnya desain non-randomized control group, pretest-posttest. Desain tersebut dipilih karena subjek penelitian tidak dapat diacak secara bebas karena kelas sudah tersedia dan tidak memungkinkan untuk membentuk kelas baru. Subjek penelitian ini adalah siswa kelas sepuluh yang kemudian dijadikan sample setelah diacak menggunakan cluster sampling. Instrumen yang digunakan dalam pengumpulan data adalah tes yang meliputi: a) pretes (untuk mengetahui apakah kemampuan awal subjek telah sama) dan b) posttes (untuk mengetahui perbedaan signifikan antar subjek setelah pengunaan strategi SMART). Setelah semua data terkumpul, datapun dianalisis menggunakan SPSS 20. Hasil dari penelitian ini menunjukkan bahwa strategi SMART dapat membantu siswa memahami bacaan teks biografi. Perbedaan antara subjek yang menggunakan strategi SMART tergolong signifikan karena berdasarkan tes Levene hasilnya adalah 0.009 yang benar-benar kurang dari 0.05. Rata-rata pada kelas eksperimen yang adalah 77.875, sedangkan pada kelas kontrol rata-ratanya 69.625. Setelah dianalisis menggunakan eta-square, hasil dari penggunaan strategi SMART menunjukkan angka 0.11 yang tergolong dalam efek sedang. Kata kunci: strategi SMART, kemampuan memahami bacaan, teks biografi